French-Spanish Translation of Legal-Institutional Texts: Main Parameters Aimed at Students - Castellano Martínez, José María (Íkala, Revista de Lenguaje y Cultura, 2011)
In this paper an analysis is made of the main characteristics of both French and Spanish legal speech in order to propose different translation strategies for students of Translation & Interpretation Studies to follow depending on lexical-semantic aspects, in particular, those that frequently appear in the writing and translation processes of legal documents in French. After an introduction to the general characteristics of legal speech, we study the more relevant lexical and semantic aspects of French legal language. All these questions are accompanied, not only by different proposals of translation but examples also based, above all, on the main French codes. At the end, a comparative table of the most representative legal and political institutions from France and Spain is offered with some suggestions about possible techniques to take into account for translation.